Challenges in machining composite materials: impact of machining parameters on cutting force - Mohamad, Nurhaniza; Mohd Ariffin, Mohd Khairol Anuar; Mustapha, Faizal; Baharudin, B.T Hang Tuah (ModTech Publishing House, 2023)
In the aerospace sector, a hybrid material called CFRP-Aluminum composite is frequently employed. The machining of composite laminate determines the surface integrity and surface polish of the machine part. Excessive cutting forces must be avoided during machining since they are one of the main factors that cause machining problems. By doing this, it is made sure that no waste material is produced during the last phases of production. It is essential to select suitable and perfect machining settings to accomplish the lowest pressure during machining activities. In this study, the issues during the process of CFRP-Aluminum composites milling will be discussed that help utilise various parameters of cutting. A design of experiments method (DOE) was used to run trials with a range of parameter values and levels. Cutting force impacts of machining parameters are assessed by combining Taguchi and statistical analysis of variance (ANOVA). The resulting machining power, which accounts for 54.23 percent for S1 and S2 and 73.57 percent for S2, has the greatest influence on the depth of cut. The feed rate, which accounts for 45.19 percent of the variance in workpiece stiffness and strength, is the factor that has the greatest impact on S3 force. The outcomes proved that there is an adverse correlation exists between cutting forces on one side and feed rate, depth of cut, and cutting speed on the other hand. The results also showed that while the feed rate is set 800 mm/min, the depth of cut is considered 0.2 mm and the spindle speed is set 5000 RPM, the machining force will be minimized.